2014
DOI: 10.1007/s11306-014-0718-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis reveals insights into biochemical mechanisms of mental stress-induced left ventricular dysfunction

Abstract: Mental stress induced left ventricular dysfunction (LVD) has been associated with a greater risk of adverse events in coronary heart disease (CHD) patients independent of conventional risk indicators. The underlying biochemical mechanisms of this cardiovascular condition are poorly understood. Our objective was to use metabolomics technology to identify biochemical changes that co-occur with mental stress-induced LVD in patients with clinically stable CHD. Participants were adult CHD patients who were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…During periods of oxidative stress, mitochondria become less capable in converting ADP to ATP. This results in ADP to be shunted to the production of hypoxanthine which is associated with an increase of uric acid35, as observed in STEMI patients (Fig. 3B).…”
Section: Discussionmentioning
confidence: 60%
“…During periods of oxidative stress, mitochondria become less capable in converting ADP to ATP. This results in ADP to be shunted to the production of hypoxanthine which is associated with an increase of uric acid35, as observed in STEMI patients (Fig. 3B).…”
Section: Discussionmentioning
confidence: 60%
“…The signals were assigned by comparing their chemical shift and multiplicity with Chenomx software data bank (Chenomx Inc., Canada, ver 8.02). Literature on previous quantitative investigations conducted with the same technique reports a precision error below 2% [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, researchers have also begun to examine the metabolome, or the detailed profile of metabolites in the body, in relation to stress in animals and, to some degree, in humans, with some evidence for metabolome differences related to psychosocial stress and obesity . The very few studies to consider this in children have found some differences between children with obesity and lean children (e.g., amino acid patterns ) but also yielded mixed results .…”
Section: Evidence For Biological Mechanisms Connecting Early Life Strmentioning
confidence: 99%